Βιβλιοκρισία: A. TADDEI, Hagia Sophia before Hagia Sophia. A study of the Great Church of Constantinople from its origins to the Nika Revolt of 532 [Saggi di storia dell’ arte, 52]. Rome: Campisanto Editore, 2017. - ΑΛΜΠΑΝΗ, Τζενη (Byzantina Symmeikta, 2019)
Alessandro Taddei, Hagia Sophia before Hagia Sophia. A study of the Great Church of Constantinople from its origins to the Nika Revolt of 532 [Saggi di storia dell’ arte, 52]. Rome: Campisanto Editore, 2017.